2017
DOI: 10.3390/cryst7060172
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electrical Properties Characterization of Sb1.52Bi0.48Te3.0 Melt-Spun Ribbons

Abstract: Melt-spinning (MS) has been reported as a promising tool to tailor the microstructure of bulk thermoelectric materials leading to enhanced thermoelectric performances. Here, we report on a detailed characterization of p-type Bi 0.48 Sb 1.52 Te 3 ribbons produced by melt-spinning. The microstructure of the melt-spun ribbons has been studied by means of X-ray diffraction, scanning and transmission electron microscopy (TEM). The analyses indicate that the ribbons are highly-textured with a very good chemical homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 56 publications
5
13
0
Order By: Relevance
“…PXRD patterns of the BixSb2-xTe3 samples: a) reference and melt-spun samples for x = 0.40, b) magnification of the region around the (015) peak. The PXRD patterns of the Ref andMS x = 0.48 samples are similar and can be found in our prior study[20].…”
supporting
confidence: 83%
See 3 more Smart Citations
“…PXRD patterns of the BixSb2-xTe3 samples: a) reference and melt-spun samples for x = 0.40, b) magnification of the region around the (015) peak. The PXRD patterns of the Ref andMS x = 0.48 samples are similar and can be found in our prior study[20].…”
supporting
confidence: 83%
“…detectable. This result can be attributed to the very high cooling rate undergone by the melt during the MS process that leads to homogeneous ribbons, as shown in our previous study [20].…”
Section: Microstructure and Chemical Homogeneitysupporting
confidence: 70%
See 2 more Smart Citations
“…Also, in nanostructured Bi 2 Te 3 /MnTe 2 , the ZT was found to be 0.26 at 480 K. 157 The sintered bulk materials of p-type Bi 0.52 Sb 1.48 Te 3 prepared using melt spinning and rapid sintering were found to depend on thermal conductivity of ambient gases with enhancement in ZT value of about 1.09 at 340 K. 158 To control the crystallographic preferred orientation, melt spinning method has been applied for CHI 3 -doped Bi 2 Te 2.4 Se 0.6 alloys with an optimized frequency of 300 rpm with ZT of 1.02 at 400 K. 119 The outstanding homogeneity and reproducibility by varying the stoichiometry have played a crucial role in the transport properties of p-type Bi x Sb 2−x Te 3 prepared by melt spinning. 159 The bulk materials of p-type Bi 0.52 Sb 1.48 Te 3 were synthesized by Yun et al, 160 and it was observed that an argon atmosphere could effectively inhibit heat loss and suppress the sublimation of tellurium. Therefore, the Bi 0.52 Sb 1.48 Te 3 sample showed the highest ZT of 1.09 at 340 K (Fig.…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%